Investigation of the Electromagnetic Fields in Gyrotropic Waveguides - Malisauskas, V.; Sledevic, T. (Elektronika ir Elektrotechnika, 2011)
In this paper a general algorithm, program in MATLAB environment and technique to investigate electomagnetic (EM) fields in gyrotropic waveguides are created. To test them distribution of EM fields of models H01, HE11 were investigated in dielectric waveguides. Distribution of EM fields of mode HE11 in gyroelectric semiconductor and semicinductor-dielectric n-InSb waveguides are investigated. Dependence of distribution of EM fields of the hybrid main mode HE11 in semiconductor n-InSb waveguides on normalized frequency and external dielectric layer is defined.